RELOKASI HIPOSENTER GEMPA MIKRO DENGAN METODE SED DAN JHD SEBAGAI ANALISIS RESERVOAR AREA PANAS BUMI-X - Cassandra Fitrianna Idat; Udi Harmoko (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2016)
Mount Wayang and Windu, located about 35 kilometers south of Bandung, the capital of West Java, Indonesia. This area included in a set of active hydrothermal geothermal area around South Bandung. Microearthquake network is a collection of microearthquake recording station that has been used from 1960. Data from this network of micro earthquakes can predict permeable structure in the reservoir, which is as monitoring the pattern of fluid flow and reservoir limits, called cap rock that is impermeable. Analysis of seismic activity in micro earthquake data that is in determining the location of the hypocenter, for determining the location of the hypocenter can complicate the interpretation of the structure. Methods Single Event Determination (SED) and the Joint Hypocenter Determination method (JHD) can optimize the location of the hypocenter with a correction to the 1-D velocity model. There are 160 events were recorded from January 2014 to April 2014. The data is processed so that there are 55 local earthquake event data were inverted to obtain new hypocenter location using the SED and JHD. The second result of inversion produces more accurate hypocenter locations with a reservoir that has a moment epicenter distribution pattern direction Northwest - Southeast. Long reservoir SED results estimated 25 km with a depth of permeable zone of 20 km, whereas after correction obtained JHD same length but permeable zone is detected to a depth of 26 km. Keywords: Joint Hypocenter Determination, Single Event Determination, Microearthquake, Geothermal.